Effect of Alkaline Conditions on the Linalool Retention Ability of Dried Starch matrices - Chanjarujit, Wathanamon; Chaiseri, Siree (Journal of Food Technology, Siam University, 2018)
This research studied the effect of calcium hydroxide (Ca(OH)2) and sodium hydroxide (NaOH) cooking on the retention of linalool in dried starch matrices. The results showed that the Ca(OH)2-cooked starch matrix was highly effective in retaining linalool, both in freshly prepared and stored samples. In freshly cooked sample, it entrapped 34.40 + 5.5 mg linalool/g matrix, increased 13-folds more than that entrapped in water-cooked starch matrix. Moreover, the Ca(OH)2-cooked starch matrix retained 92.2% linalool after storage at 53% RH, 25oC for 4 months. The tightening of Ca(OH)2-cooked starch network caused by Ca-starch crosslinks, and the matrix thickness affected the linalool retention. Conversely, the fresh NaOH-cooked starch matrix showed the poor linalool entrapment. This research suggests that cooking starch under alkaline condition with the presence of calcium increased the retention of flavor compound in dried starch matrix.